An Impossible Task? Australian Food Law and the Challenge of Novel Meat Analogues. (September 2022) - Johnson, Hope; Parker, Christine
This paper asks what the regulatory assessment of the novel processed meat analogue products reveals about the nature of food regulation in Australia. We analyse Food Standards Australia and New Zealand's ('FSANZ') assessment of the recent application by Californian technology company Impossible Foods Inc to sell its proprietary burger products which contain a genetically modified protein that is said to make their burger 'bleed'. We show that FSANZ's assessment process has little capacity to engage with broader and longer term, social, ecological and public health implications of novel foods and changing food markets. FSANZ's regulatory pre-approval process focuses almost exclusively on the safety of individual ingredients rather than the impact of novel foods on the food supply as whole and leaves broader issues to the market and consumer choice with limited support from laws addressing misleading labelling and marketing of foods. Extending the capacity of Australia's regulatory regime for food to deal with more than the safety of individual ingredients will become more urgent as other novel foods, such as cell-based meats, enter the marketplace.